1992
DOI: 10.1097/00001888-199207000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of expert and non-expert facilitators on the small-group process and on student performance

Abstract: At the University of Michigan Medical School in 1990, the authors investigated the effects of faculty facilitators' levels of content expertise on the educational process and learning outcomes of small-group teaching sessions. The study was conducted in a microbiology course for second-year students in which four small-group sessions were used to replace 38 hours of lecture and laboratory time. The interactions between 11 expert and ten non-expert faculty facilitators and 156 students were observed and coded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 0 publications
5
80
2
Order By: Relevance
“…In a CBL approach, this includes his or her understanding of the targeted problem space afforded by the specific case under discussion. Research has demonstrated a relationship between a facilitator's content expertise and student satisfaction (Davis, Nairn, Paine, Anderson, & Oh, 1992) and achievement (Davis et al, 1992;Schmidt, Van Der Arend, Moust, Kokx, and Boon, 1993), as well as instructor facilitation style (Gilkison, 2003;Groves, Régo, & O'Rourke, 2005). This is similar to what Bond, Smith, Baker, and Hattie (cited in Berliner, 2001) reported in their extensive comparison of expert and non-expert teachers: the greatest discriminator between these two groups was the expert teachers' abilities to create and provide deep representations of the subject matter.…”
Section: Content Expertisesupporting
confidence: 72%
“…In a CBL approach, this includes his or her understanding of the targeted problem space afforded by the specific case under discussion. Research has demonstrated a relationship between a facilitator's content expertise and student satisfaction (Davis, Nairn, Paine, Anderson, & Oh, 1992) and achievement (Davis et al, 1992;Schmidt, Van Der Arend, Moust, Kokx, and Boon, 1993), as well as instructor facilitation style (Gilkison, 2003;Groves, Régo, & O'Rourke, 2005). This is similar to what Bond, Smith, Baker, and Hattie (cited in Berliner, 2001) reported in their extensive comparison of expert and non-expert teachers: the greatest discriminator between these two groups was the expert teachers' abilities to create and provide deep representations of the subject matter.…”
Section: Content Expertisesupporting
confidence: 72%
“…For example, some researchers recommend that tutors be content experts or faculty with facilitation training (Barrows, 1996;Bochner et al, 2002;Gilkison, 2003;Schmidt & Moust, 1995;Schmidt, Van Der Arend, Moust, Kokx, & Boon, 1993;Schmidt et al, 1994). An early effort that characterizes the impacts of tutor expertise in relation to faculty direction of students (Albanese & Mitchell, 1993) found that expert tutors provide less engagement for student-directed discussion and learning (Davis, Nairn, Paine, Anderson, & Oh, 1992;Silver & Wilkerson, 1991) and were more likely to intervene in student-directed discussion (De Volder, 1982). Since the goal of PBL is to promote self-directed learning, these seem to provide a rationale against the use of expert tutors.…”
Section: Tutor Content Expertisementioning
confidence: 99%
“…PBL tutors must understand how their role as a tutor changes during the course of a particular problem. In addition, tutors should have a great deal of familiarity with the problem and common approaches to solving it, either as a result of closely collaborating with the case designer or by co-authoring the instructional materials (Chan, 2008;Davis et al, 1992;Johansen, Martenson, & Bircher, 1992). Despite uniform calls for training, some studies have openly used inexperienced tutors with little training (Steinkuehler, Derry, Hmelo-Silver, & Delmarcelle, 2002), but those studies are the exception rather than the norm.…”
Section: Tutor Training and Experiencementioning
confidence: 99%
“…A number of studies have investigated the relationship between the tutor's background and learning outcomes, including the quality of the learning processes (Moust and Schmidt 1994;Maudsley 1999;Solomon and Crowe 2001;Matthes et al 2002;Kassab et al 2005a;Moore and Kain 2011), but their conclusions are inconsistent. Some studies show that there are advantages in having content-expert tutors in promoting positive learning outcomes (Davis et al 1992;Schmidt et al 1993) while others have found that no such difference exists (Regehr et al 1995;Dolmans et al 1996).…”
Section: Introductionmentioning
confidence: 99%